Philippine eSports Training Center for extended reality technologies - Presbitero, Aldritz F.
Esports has taken the spotlight as one of the growing industries in recent times. eSports being sedentary in nature, has been associated with several health risks. eSports athletes experience physical and mental health issues due to the training conditions and lack of purpose-built facilities that will accommodate their unique needs. The green mind theory (GMT) suggests that having a green mind produces positive behaviors that shape the environment. GMT comprises 4 key principles: Place-making, Habits into routine, Immersion to interactive activities, Natural and social engagement. These components are the strategies to achieve a ‘green mind’. The emergence of extended reality (XR) technologies creates an innovative approach in promoting physical activity for eSports athletes. Virtual reality (VR) exergames immerse eSports athletes into a new variety of physical and mental training in improving their eSports performance. Incorporating both concepts, the designer reshapes and reimagines a new eSports training facility that will promote health and well-being for eSports athletes. Taking into account the influence of COVID-19 pandemic, it is significant to realize the changes of our social behaviors that affect our physical environment. Adjustments to the ‘new normal’ through transition spaces are necessary in reconnecting eSports athletes with the ‘outside world’